2011
DOI: 10.1074/jbc.m111.245258
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of SlyA Protein, a Master Virulence Regulator of Salmonella, in Free and DNA-bound States

Abstract: SlyA is a master virulence regulator that controls the transcription of numerous genes in Salmonella enterica. We present here crystal structures of SlyA by itself and bound to a highaffinity DNA operator sequence in the slyA gene. SlyA interacts with DNA through direct recognition of a guanine base by Arg-65, as well as interactions between conserved Arg-86 and the minor groove and a large network of non-base-specific contacts with the sugar phosphate backbone. Our structures, together with an unpublished str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
98
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 28 publications
10
98
0
Order By: Relevance
“…With the exception of P62A, these residues will not be considered further based on their lack of effect. The homologous proline in the MepR homologue SlyA of Salmonella enterica (P61) does have functional significance in that the structural analysis of cocrystallized SlyA and cognate DNA revealed that P61 makes van der Waals contacts with nucleobases in the major groove (23,24). Either MepR P62 does not play a similar role, or an alanine can substitute completely for any P62-base contact.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of P62A, these residues will not be considered further based on their lack of effect. The homologous proline in the MepR homologue SlyA of Salmonella enterica (P61) does have functional significance in that the structural analysis of cocrystallized SlyA and cognate DNA revealed that P61 makes van der Waals contacts with nucleobases in the major groove (23,24). Either MepR P62 does not play a similar role, or an alanine can substitute completely for any P62-base contact.…”
Section: Resultsmentioning
confidence: 99%
“…MarR homologues control pathways that are critical to bacterial physiology such as stress responses (41,42), virulence (43), metabolism (10), and multiple-drug resistance (23,44,45). The activity of a subset of these proteins can be modified through the formation of a disulfide bond (19,41,46).…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, no overall correlation exists between ΔG SC and Leu phenotype in the four strains. Instead, a Leu + phenotype correlates with the absence of DNA topoisomerase I (TopA − ) other proteins that bind to A + T-rich DNA, including proteins that bind using a winged helix-turn-helix motif (Brennan 1993;Dolan et al 2011;Kenney 2002;Martínez-Hackert and Stock 1997). Here, the protein is interacting with both the major groove (where the DNA base sequence is accessible) and the minor groove (where a specific DNA sequence is not being sought).…”
Section: Protein Binding As a Function Of Dna Topologymentioning
confidence: 99%